KETERKAITAN HARGA DIRI DAN ANSIETAS: STUDI MAHASISWA DI YOGYAKARTA - Sabita Hanifa Riyanti; Murdhiono, Wahyu Rochdiat; Khasanah, Nur; Riska, Herliana (Jurnal Keperawatan Malang, 2025)
Background: Students have the potential to experience anxiety in their learning process. Low self-esteem can trigger students' concerns about their academic achievements in the future. Excessive anxiety will also interfere with their learning process so that their academic achievement can decrease. Purpose: This study aims testing the relationship between self-esteem and anxiety levels of students in Yogyakarta Methods: A quantitative approach with cross sectional design. The research sample consisted of 596 students from 11 universities in Yogyakarta which was conducted online using a zoom meeting link for detailed explanations and a google form for filling out the questionnaire. Data were collected using the Rosenberg Self – Esteem Scale (RSES) and the Depression Anxiety Stress Scale (DASS-21). Result: The results of the analysis show that there is a negative relationship between self-esteem and anxiety levels (p <0.05). The higher a person's self-esteem, the lower their anxiety levels. This finding indicates that self - esteem plays an important role in influencing anxiety levels in students. Implication: The results of this study can be used as a basis for implementing intervention strategies aimed at strengthening self-esteem and reducing anxiety in students.